The Eï¬€ect of Pelvic Rocking Exercise and Buteyko Exercise on Reducing Primary Dysmenorrhea Pain Levels - Diana Rhismawati Djupri; Irfan Said; Hanik Rohmah Irawati; Saskiyanto Manggabarani (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Dysmenorrhea is cramping pain and is often followed by lower back pain, nausea and vomiting, headache and diarrhea. Dysmenorrhea refers to the overall pain symptoms that arise during menstruation, there are 2 types of dysmenorrhea, namely, primary and secondary dysmenorrhea. is a cyclic menstrual pain without pathological abnormalities in the pelvis is called Primary dysmenorrhea. There are 2 types of Management primary dysmenorrhea which are pharmacological and non-pharmacological. The treatment for Non-pharmacological can be done with pelvic rocking exercise and Buteyko Exercise. The movements in pelvic rocking exercise and Buteyko Exercise can stimulate the body to release endorphins which function as natural sedative hormones, and can also facilitate blood flow to the uterus so that pain is reduced. Purpose:The effect of pelvic rocking exercise and Buteyko Exercise on reducing pain in primary dysmenorrhea was the purpose of this research. Methods: This research is a quantitative study with a quasi-experimental design, pre-test and post-test designs. Nonequivalent control group design. The amount of the sample are 58 people by using purposive sampling technique. The research instrument used a standard operating procedure sheet for pelvic rocking exercise and Buteyko Exercise, a monitoring sheet, a stop watch and a numeric rating scale pain measurement sheet. The hypothesis is tested by using the independent T Test. Results: Before the intervention, the p-value was 0.063. The results of this research was p value 0.001. Conclusion: This research can also be used as input for nurses to make new decisions in improving the quality of nursing care with non-pharmacological therapeutic approaches. There is an effect of pelvic rocking exercise and Buteyko Exercise on reducing pain in primary dysmenorrhea. The results of this research can be used as a contribution of thoughts and references as a more in-depth study of pain reduction in primary dysmenorrhea.